Risk of Cardiovascular Events and Medical Cost of Dapagliflozin and Dipeptidyl Peptidase-4 Inhibitors - Seong, Jong-Mi; Kim, Jong Joo; Kim, Hae Jin; Sohn, Hyun Soon (Frontiers in Pharmacology, 2021)
This study compared dapagliflozin, a sodium-glucose co-transporter 2 inhibitor, and dipeptidyl peptidase-4 inhibitors (DPP-4i) with regard to cardiovascular (CV) event incidence and direct medical costs during type 2 diabetes treatment. A retrospective cohort study was conducted using national health insurance claims data from September 1, 2014, to June 30, 2018, of patients in Korea. Patients who were prescribed dapagliflozin and DPP-4i for the first time were included. The primary outcome was the incidence of a composite of major adverse CV events (MACEs)—nonfatal myocardial infarction, nonfatal stroke, or in-hospital CV death. Proportional hazard models after propensity score weighting were used to determine hazard ratios (HRs) and 95% confidence intervals (CIs) for MACE in the dapagliflozin and DPP-4i groups. A decision analytic model was used to compare direct medical costs between the two treatment groups from a healthcare provider’s perspective. Of the 260,336 patients in the cohort, 23,147 and 237,189 received dapagliflozin and DPP-4i, respectively. During the follow-up, 184 patients receiving dapagliflozin and 3,674 receiving DPP-4i (incidence, 6.47 and 11.33 events/1000 person-years, respectively) had MACE. The adjusted HR of MACE for dapagliflozin compared with that for DPP-4i was 0.69 (95% CI 0.57–0.83). The corresponding HRs were consistent among patients with and without underlying CV disease. The estimated direct medical cost appeared to be lower by $68,452 in the dapagliflozin group than that in the DPP-4i group for 3 years, in 1,000 hypothetical patients. In this population-based cohort study, the use of dapagliflozin instead of DPP-4i was associated with a reduced risk of MACE, which subsequently reduced direct medical costs. These data provide valuable information to patients, practitioners, and authorities regarding the risk of CV events associated with dapagliflozin versus DPP-4i use in clinical practice.